Can We Validate the Value? Valuing Automotive and Component Sub-Sector Companies Listed on the Indonesia STOCK Exchange during the Covid-19 Pandemic Crisis - Soelistyo, Alex; Hendrawan, Riko (International Journal of Multidisciplinary: Applied Business and Education Research, 2022)
This study provides a comprehensive fundamental-based value analysis of firms using Discounted Cash Flow (DCF) and Relative Valuation (RV) approaches. This study reveals how these approaches behave in valuing firms during a crisis such as the one caused by the current covid-19 pandemic and how to validate the results as well as correct them if the results was invalid. The object of the study is companies in the automotive and component sub-sector listed in Indonesia Stock Exchange (IDX) in 2020. The company's historical financial data between 2016 and 2020 are used to predict its financial behavior over the next five years under three scenarios: optimistic, moderate, and pessimistic. From the study employing the DCF method, the following results were obtained: ASII and INDS stocks were overvalued in all scenarios, GJTL were undervalued in all scenarios, and SMSM were overvalued in pessimist and moderate scenarios while undervalued in optimist scenario. Correction upon intrinsic values of SMSM and ASII is required since the result from RV analysis imply that the DCF results of both companies are not entirely valid, which indicates that the pandemic crisis has significantly affected the value of both companies. Investment recommendations for both ASII and INDS were to sell the stocks while for both SMSM and GJTL were to buy the stocks.